PENGARUH MOTIVASI TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK PENGHASILAN ORANG PRIBADI USAHAWAN (STUDI DI SENTRA PRODUKSI MANIK-MANIK DESA PLUMBONGAMBANG, KECAMATAN GUDO, KABUPATEN JOMBANG, PROVINSI JAWA TIMUR) - AYUVISDA SULISTIYONO, ADINCHA Ayuvisda (Jurnal Akuntansi AKUNESA, 2012)
The purpose of this research is to see the effect of motivation on taxpayer compliance in the payment of Personal Income Tax in the industrial Entrepreneur beads Plumbon Gambang village. Inferential data processing analysis tool that uses two confirmatory factor analysis to determine the contribution of each indicator of motivation, compliance and simple linear regression analysis to determine the effect of motivation on adherence to pay taxes. The results showed extrinsic factors contribute most strongly to the motivation, the accuracy of the filling factor contributing the most powerful SPT to pay tax compliance, test results obtained statistically significant positive effect on adherence motivation to pay taxes, but the effect is still weak is only about 47.1%. Keywords: Motivation Taxpayer, Taxpayer Compliance Rate